Narcolepsy - Clinical Characteristics, Aetiopathophysiology, Diagnosis and Treatment- A Global Review: Pharmaceutical Science-Pharmaceutical Sciences - Koppuravuri, Naga Prashant; N, Sangeetha; U R, Thasvin; Pasha, T Y; V, Rajesh Venkataraman; Siva Ganesh, V (International Journal of Life Science and Pharma Research, 2022)
Narcolepsy is a rare chronic, debilitating sleep disease that is currently categorized as different types of CNS hypersomnia in narcolepsy type 1 (NT1) and narcolepsy type 2 (NT2). Narcolepsy type 1 (NT1) is narcolepsy with cataplexy caused by a selective loss of hypothalamic neurons that produce hypocretin, while NT2 is narcolepsy without cataplexy and normal hypocretin levels. Hypocretin is a neurotransmitter that regulates sleep, body homeostasis, emotions, and behavior and has extensive projections to a variety of brain locations, including the locus coeruleus (norepinephrine neurons), tuberomammillary nucleus, raphe nucleus (serotonergic neurons), and dopaminergic neurons (ventral tegmental areas). Hypocretin is a neurotransmitter that not only excites the central nervous system, but also affects serotonin and histamine levels. Hypocretin is a neurotransmitter that regulates the activity of serotonin, histamine, dopamine, acetylcholine, GABA, and glutamate in the central nervous system. It is now understood to be a separate condition with its own pathogenesis and neurochemical abnormalities. Narcolepsy affects men and women equally and has a prevalence of 20–60 cases per 100,000. The highest rate is found in Japan, while the lowest is found in Israel. There is no cure for narcolepsy, despite a reliable pathophysiological hypothesis linking NT1 to an autoimmune process that damages hypocretin-producing cells. Because current symptomatic pharmaceutical treatments are not 100% effective for all symptoms, behavioral therapies play a synergistic role in the disease treatment. We examine the narcolepsy diagnostic and treatment options, including symptomatic pharmacological treatments as well as behavioral and psychological measures that may help doctors to improve narcoleptic patients' quality of life.